Activation of the transcription factor, nuclear factor kappa-B, during the estrous cycle and early pregnancy in the pig - Hayashi Kanako; Ritchey Jerry W; Reagan Patrick; Mathew Daniel; Ashworth Morgan D; Ross Jason W; Spencer Thomas E; Lucy Matthew; Geisert Rodney D (BMC, 2010)
Abstract Establishment and maintenance of pregnancy in the pig involves intricate communication between the developing conceptuses and the maternal endometrium. This process occurs during trophoblast elongation which is spaciotemporally associated with conceptus synthesis and release of IL1B concomitant with pregnancy-specific endometrial up-regulation of IL-1 receptors, providing the potential for activation of the transcription factor, NFKB. The objective of the current investigation was to determine changes in expression and cellular localization of NFKB and associated factors during the estrous cycle and early pregnancy in the pig. In situ hybridization was used to localize changes in PGR, ESR1, and TNFRSF11A during the peri-implantation period. Quantitative RT-PCR was utilized to demonstrate gene expression changes for NFKB1, RELA, TNFRSF11A, TLR4, NFKBIA and NFKBIB. Transcription factor ELISA demonstrated an overall increase in RELA during the peri-implantation period in both cyclic and pregnant gilts. While the presence of TNFSF11A and TLR4 were both detected, TLR4 expression changes were temporally associated with NFKB expression and activation. Collectively, these data demonstrate that NFKB activation may occur during the period of uterine receptivity in both the cyclic and pregnant endometrium.